Surgical Outcomes After Neoadjuvant Chemoimmunotherapy for Resectable Non-Small Cell Lung Cancer - Hu, Yan; Ren, Si-Ying; Wang, Ruo-Yao; Zeng, Chao; Li, Ji-Na; Xiao, Peng; Wu, Fang; Yu, Feng-Lei; Liu, Wen-Liang (Frontiers in Oncology, 2021)
Background Neoadjuvant chemoimmunotherapy for resectable non-small cell lung cancer (NSCLC) represents an important research topic. Despite the potential benefits of this approach, the inflammatory responses and adverse events associated with neoadjuvant chemoimmunotherapy can present technical challenges and compromise a planned resection. This study assessed the safety and feasibility of neoadjuvant chemoimmunotherapy followed by surgery for resectable NSCLC. Methods The study was conducted from May 2019 to March 2021. Patients who were age 18 years or older, were diagnosed with stage Ib-IIIb NSCLC, and received neoadjuvant chemoimmunotherapy followed by surgery were included. Demographic information, clinical and pathologic characteristics, data about neoadjuvant therapy, and surgical details were collected by retrospective chart review. Toxicity profiles were collected retrospectively or by telephone follow-up. Results Twenty patients were included in this study. The median age was 56 years (range, 48–72 years), and 18 patients (90%) were men. Squamous carcinoma (14/20, 70%) was the most common cancer type, followed by adenocarcinoma (4/20, 20%), adenosquamous carcinoma (1/20, 5%), and large cell neuroendocrine carcinoma (1/20, 5%). All patients received 2–4 cycles of neoadjuvant therapy, and the median interval between final therapy and surgery was 49 days (range, 23–133 days). Computed tomography evaluation after neoadjuvant therapy showed partial response in 15 patients (75%) and stable disease in 5 (25%). Final pathologic examinations showed major pathologic response in 8 patients, including pathologic complete response in 5 (25%). Most patients (18/20, 90%) had reduced pathologic staging. Twelve patients (60%) underwent open thoracotomy; the other 8 patients underwent minimally invasive surgery, which was uneventful and without intraoperative conversion to open thoracotomy. No perioperative deaths occurred, and only 7 patients (35%) developed postoperative complications. Most patients experienced only grade 1–2 adverse effects and laboratory abnormalities during neoadjuvant therapy, and no grade 3 or worse adverse effects or laboratory abnormalities occurred. No patients experienced surgical delays as a result of immune-related adverse events. Conclusions Preoperative administration of chemoimmunotherapy for patients with resectable NSCLC was safe and feasible.